2008
DOI: 10.1182/blood-2007-12-128744
|View full text |Cite
|
Sign up to set email alerts
|

ASB2 targets filamins A and B to proteasomal degradation

Abstract: The ordered series of proliferation and differentiation from hematopoietic progenitor cells is disrupted in leukemia, resulting in arrest of differentiation at immature proliferative stages. Characterizing the molecular basis of hematopoietic differentiation is therefore important for understanding and treating disease. Retinoic acid induces expression of ankyrin repeat-containing protein with a suppressor of cytokine signaling box 2 (ASB2) in acute promyelocytic leukemia cells, and ASB2 expression inhibits gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
126
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(141 citation statements)
references
References 43 publications
15
126
0
Order By: Relevance
“…Western blotting, immunofluorescence, and flow cytometry assays, we previously showed that ASB2␣ expression triggers polyubiquitination and proteasomal degradation of filamins (5)(6)(7)31). In keeping with our earlier studies (7), flow cytometric degradation assays show that the FLNa ABD is both necessary and sufficient for ASB2␣-mediated degradation as the isolated ABD is efficiently degraded following ASB2␣ expression, although FLNa lacking the ABD is resistant to degradation (Fig.…”
Section: Asb2␣ Targets Ch1 Of Flna For Degradation-usingsupporting
confidence: 88%
See 3 more Smart Citations
“…Western blotting, immunofluorescence, and flow cytometry assays, we previously showed that ASB2␣ expression triggers polyubiquitination and proteasomal degradation of filamins (5)(6)(7)31). In keeping with our earlier studies (7), flow cytometric degradation assays show that the FLNa ABD is both necessary and sufficient for ASB2␣-mediated degradation as the isolated ABD is efficiently degraded following ASB2␣ expression, although FLNa lacking the ABD is resistant to degradation (Fig.…”
Section: Asb2␣ Targets Ch1 Of Flna For Degradation-usingsupporting
confidence: 88%
“…We have shown that ASB2␣ expression triggers rapid proteasomal degradation of filamins in various cell types (5)(6)(7). Furthermore, retinoic acid-induced expression of ASB2␣ correlates with filamin down-regulation in myeloid leukemia cells induced to differentiate (5), and knock down of endogenous ASB2␣ delays filamin degradation and differentiation (5).…”
Section: Asb2␣mentioning
confidence: 95%
See 2 more Smart Citations
“…FLNA is a substrate for multiple kinases (reviewed in Sarkisian et al 2008) depending on whether or not its actin bound (Kawamoto and Hidaka 1984), with its cross-linking activity itself regulated by phosphorylation (Cukier et al 2007). FLN is a substrate for the Ca 2+ -activated protease calpain (Gorlin et al 1990) and for the ASB2 ubiquitin ligase (Heuze et al 2008) which provide irreversible regulatory mechanisms for severing FLN cross-links in processes requiring membrane and cytoskeleton remodelling such as cell migration (Marzia et al 2006;Baldassarre et al 2009) and receptor cycling (Seck et al 2003). FLN's role in cell motility and spreading appears to be cell-type dependent.…”
Section: Filamin Cellular Functionsmentioning
confidence: 99%